Systemic hypoxia biomarkers in asymptomatic simple non-alcoholic hepatosteatosis (African Journal of Biomedical Research, 2020)
With the dominance of its risk factors, non-alcoholic fatty liver disease (NAFLD) became common with high morbidity, nationally and worldwide. Early pathogenic implication of cellular hypoxia in asymptomatic simple non-alcoholic isolated hepatosteatosis (ANIHS) was investigated in this cross-sectional study and correlated changes in systemic hypoxia biomarkers with body mass index (BMI) in apparently healthy ANIHS participants with normal liver enzymes and size. We enrolled 180 adult consented volunteering Saudi participants in the period from January 1 to June 1, 2019. They comprised of normal lean healthy controls (n = 40; BMI = 18.5-25) and ANIHS participants (n 140) that were subdivided as overweight (n = 64; BMI = 25.1 – 30) and obese (n = 76; BMI >30 -